NAT2 gene polymorphisms in three indigenous groups in the Colombian Caribbean Coast region (2023)
Objective: To study the NAT 2 gene polymorphisms 481T, 590A and 857A in the Chimila, Wiwa and Wayuu indigenous groups of the Colombian Caribbean to determine the frequencies of the alleles NAT2*4, NAT2*5, NAT2*6, and NAT2*7 and to determine the types of acetylators present in these populations. Methods: A total of 202 subjects were studied: 47 Chimila, 55 Wiwa, and 100 Wayuu. Te polymorphisms were identifed using a real-time PCR method for allelic discrimination designed using Taqman of Applied Biosystems. Results: Te following alleles were found at the highest frequency in the following groups: the NAT2*4 allele (wild type) in the Wayuu group (55.3%), the NAT2*5 allele in the Wiwa group (34.5%), and the NAT2*7 allele in the Chimila group (24.2%). A higher frequency of the rapid acetylator status was found in the Wayuu group (31.3%) and Chimila group (29.5%) compared with the Wiwa group (12.7%). Te intermediate acetylator status distribution was very similar in all three groups, and the frequency of the slow acetylator status was higher in the Wiwa group (32.7%) compared with the Chimila and Wayuu groups (20.5% and 21.2%, respectively). Conclusion: Te results demonstrated the allelic distribution and pharmacogenetic diferences of the three groups studied and revealed the most frequent acetylator status and phenotype. Because of the high prevalence of slow acetylators, a greater incidence of tuberculosis (TB) drug-induced hepatotoxicity is predicted in these populations, with a higher frequency in the Wiwa group. © 2014 Universidad del Valle.